Prognostic value of haemoglobin drop in patients with acute coronary syndromes - Ndrepepa, Gjin; Neumann, Franz-Josef; Menichelli, Maurizio; Holdenrieder, Stefan; Richardt, Gert; Mayer, Katharina; Cassese, Salvatore; Xhepa, Erion; Kufner, Sebastian; Wiebe, Jens; Joner, Michael; Kessler, Thorsten; et al. (European Journal of Clinical Investigation, 2021)
Background: The prognostic value of in-hospital haemoglobin drop in patients with acute coronary syndrome (ACS) undergoing invasive therapy remains insufficiently investigated. Materials and Methods: This observational study included 3838 patients with ACS with admission and in-hospital nadir haemoglobin values available. Haemoglobin drop was defined as a positive difference between admission and nadir haemoglobin values. The primary endpoint was one-year all-cause mortality. Results: In-hospital haemoglobin drop occurred in 3142 patients (82%). Patients were categorized into 4 groups: no haemoglobin drop (n = 696 patients), <3 g/dl haemoglobin drop (n = 2703 patients), 3 to <5 g/dl haemoglobin drop (n = 344 patients) and ≥5 g/dl haemoglobin drop (n = 95 patients). The primary endpoint occurred in 156 patients: 17 patients (2.5%) in the group with no haemoglobin drop, 81 patients (3.0%) in the group with <3g/dl haemoglobin drop, 37 patients (10.9%) in the group with 3 to <5 g/dl haemoglobin drop and 21 patients (22.2%) in the group with ≥5 g/dl haemoglobin (adjusted hazard ratio [HR] = 1.30, 95% confidence interval 1.17 to 1.45; p <.001 for one g/dl haemoglobin drop). The association of haemoglobin drop with one-year mortality remained significant after exclusion of patients with in-hospital overt bleeding (adjusted HR = 1.27 [1.11–1.46]; p <.001 for one g/dl haemoglobin drop). The lowest haemoglobin drop associated with mortality was 1.23 g/dl in all patients (HR = 1.03 [1.02–1.04]) and 1.13 g/dl in patients without overt bleeding (HR = 1.03 [1.01–1.04]). Conclusions: In patients with ACS, in-hospital haemoglobin drop was associated with higher risk of one-year mortality even in the absence of overt bleeding.
CRIS-Team Scopus Importer:2023-03-08
Keywords: acute coronary syndrome; bleeding; haemoglobin; mortality